Combining Digital Marketing Strategy With The Concept of Public Space in Cafe Business in Surabaya - Teguh Priyo Sadono (CV. Syntax Corporation Indonesia, 2024)
The growth of cafes in Surabaya is very rapid, reaching an average per year of 20%, even the growth after Covid 19 has increased sharper. The increase in cafes in Surabaya is driven by the increasing need for public spaces to share flavors. But on the other hand, café business competition is getting tighter, it demands creativity in implementing strategies. By asking questions about Cafe positioning and the use of Integrated Marketing Communication, this study uses a qualitative method approach to purposive samples of De Mandailing Cafe and PT Jokopi Cafe. The results obtained the use of digital marketing in an integrated manner with the concept of line and emphasis on building humanist public spaces as an answer to the communal consumer culture and lifestyle café Surabaya survived and developed as a promising Cafe Business.